2022
DOI: 10.1126/sciadv.abn4331
|View full text |Cite
|
Sign up to set email alerts
|

The two-domain elevator-type mechanism of zinc-transporting ZIP proteins

Abstract: Zinc is essential for all organisms and yet detrimental at elevated levels. Hence, homeostasis of this metal is tightly regulated. The Zrt/Irt-like proteins (ZIPs) represent the only zinc importers in metazoans. Mutations in human ZIPs cause serious disorders, but the mechanism by which ZIPs transfer zinc remains elusive. Hitherto, structural information is only available for a model member, BbZIP, and as a single, ion-bound conformation, precluding mechanistic insights. Here, we elucidate an inward-open metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 70 publications
(77 reference statements)
2
32
0
Order By: Relevance
“…α0a associates with α4 via hydrophobic interactions and α3 via hydrogen bonds (Supplementary Fig. 9d ), which provides a reasonable structural explanation of hyperactivation of the transporter upon α0a deletion which would otherwise limit the movement of the transport domain relative to the scaffold domain 82 . Remarkably, although the method of generating the OFC model in this work (repeat-swap homology modeling) is different from the approach used in that report (manually adjusting the position of the transport domain relative to the scaffold domain to eliminate the mismatch between the predicted contacting residues and the structure in the IFC), the two OFC models are consistent in that the transport site is lifted toward the extracellular space by ~8 Å upon the IFC-to-OFC transition (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…α0a associates with α4 via hydrophobic interactions and α3 via hydrogen bonds (Supplementary Fig. 9d ), which provides a reasonable structural explanation of hyperactivation of the transporter upon α0a deletion which would otherwise limit the movement of the transport domain relative to the scaffold domain 82 . Remarkably, although the method of generating the OFC model in this work (repeat-swap homology modeling) is different from the approach used in that report (manually adjusting the position of the transport domain relative to the scaffold domain to eliminate the mismatch between the predicted contacting residues and the structure in the IFC), the two OFC models are consistent in that the transport site is lifted toward the extracellular space by ~8 Å upon the IFC-to-OFC transition (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Lastly, the amphipathic helix (α0a, residue 7-21) solved in our structure was missed in 7Z6N. α0a associates with α4 via hydrophobic interactions and α3 via hydrogen bonds ( Figure S9d ), which provides a reasonable structural explanation of hyperactivation of the transporter upon α0a deletion which would otherwise limit the movement of the transport domain relative to the scaffold domain 82 . Remarkably, although the method of generating the OFC model in this work (repeat-swap homology modeling) is different from the approach used in that report (manually adjusting the position of the transport domain relative to the scaffold domain to eliminate the mismatch between the predicted contacting residues and the structure in the IFC), the two OFC models are consistent in that the transport site is lifted toward the extracellular space by ~8 Å upon the IFC-to-OFC transition ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 85%
“…While this manuscript was under revision, an independent study reported a structure of BbZIP in the metal-free state similarly crystallized at low pH (PDB ID: 7Z6N, referred to as 7Z6N hereafter) 82 . Contrast and comparison of two structures provide additional insights into the elevator-type transport mechanism ( Figure S9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The movement of the substrate-binding site across the membrane, and the presence of two “barriers” and two “gates” that form upon the conformational transition, indicates that the ZIP protein family members could act through moving barriers with two gates, as envisioned in the comprehensive work of Garaeva and Slotboom (2020) for the elevator-type mechanism taking place in bile acid transporter ASBT. During the revision of the present work, we became aware of a recently published manuscript describing an elevator-type mechanism for BbZIP ( Wiuf et al, 2022 ). Thus, the transport mechanism here hypothesized is fully supported by the study of Wiuf et al (2022) .…”
Section: Discussionmentioning
confidence: 99%
“…During the revision of the present work, we became aware of a recently published manuscript describing an elevator-type mechanism for BbZIP ( Wiuf et al, 2022 ). Thus, the transport mechanism here hypothesized is fully supported by the study of Wiuf et al (2022) . In conclusion, the availability of structural models for all members of the hZIP family of metal transporters will be a valuable aid in the experimental characterization of the functional details of metal transport.…”
Section: Discussionmentioning
confidence: 99%